Supramolecular architectures based on binuclear Pt(ii) complexes consisting of different ligands and circular and helical fiber structures. Issue 3 (14th December 2022) - Kim, Minhye; Ok, Mirae; Li, Chenxing; Go, Kayeong; Kim, Sehee; Kim, Juyeong; Jung, Jong Hwa; Jung, Sung Ho
Abstract : We demonstrate the control of morphologies of supramolecular architectures based on binuclear Pt(ii ) complexes through ligand changes at both end groups. Abstract : Supramolecular architectures such as helical fibers, tubular structures, and nanotoroids (nanorings) have attracted significant interest over the past few decades because of their special physical properties. In this study, we synthesized bis[terpyridine-based Pt(ii )] complexes with different terminal ligands such as Cl −, phenyl acetylene, or pyridine units. Interestingly, the binuclear terpyridine-based Pt(ii ) complex (Ch-1 ), consisting of Cl − as one ligand at both ends, formed a circular supramolecular architecture through a net structure as a thermodynamic product via multiple steps. In contrast, the Pt(ii ) complex (Ph-1 ) with phenylacetylene groups exhibited a helical fiber structure. The supramolecular architectures were generated by Pt⋯Pt, π–π, and intermolecular hydrogen-bonding interactions. In the presence of pyridine, two Cl − ligands coordinated to Pt(ii ) in Ch-1 were substituted by pyridine groups to generate a Pt(ii ) complex (Py-1 ) with pyridine groups by a ligand exchange reaction, which spontaneously afforded circular to helical fiber structures. The supramolecular architectures were generated by a cooperative pathway involving a nucleation–elongation mechanism. The helical supramolecular polymerization of Py-1 was kinetically controlled by the concentration of pyridine and followed an on-pathway.